Stability analysis of the automatic voltage regulation system with PI controller - Özdemir, Mahmut Temel; Çelik, Vedat (My University, 2017)
The system voltage is one of the most important parameters, which determines the power quality. Thestability of the system voltage is critical for the power system. This paper investigates the stability analysisof the automatic voltage regulation system controlled by a PI controller related to the controller gains. Forthis purpose, a graphical-based technique called as the stability boundary locus method is proposed in thepaper to obtain the stable parameters space of PI controller gains. Stability of closed region computed onparameters space determines from roots of characteristic equation of automatic voltage regulation system.The time-domain simulations are performed in Matlab/Simulink environment to validate the theoreticalresults.
Keywords: Mühendislik; Elektrik ve Elektronik; Fizik; Uygulamalı; Matematik